The Role of Dy3+ Ion in the Luminescence of Caal2o4: Eu2+, Nd3+, Dy3+ Phosphors - Trac, Nguyen Ngoc; Quang, Ngo Khoa; Phung, Ho Thi Kim (International Journal of Chemistry and Materials Research, 2016)
The phosphors of CaAl2O4: Eu2+, Nd3+, Dy3+ with varying concentrations of Dy3+ ion were synthesized by the combustion method. The phase structure of CaAl2O4 was investigated by X-ray diffraction. The emission spectra of phosphors have a broad band with maximum at 444 nm due to electron transition from the 4f65d1 to the 4f7 of Eu2+ ion; and a small peak of 575 nm due to 4F9/2  6H13/2 transition of Dy3+ ions. The excitation spectra and the decay time of phosphors were investigated also. The phosphors of CaAl2O4: Eu2+, Nd3+, Dy3+ have a long persistent luminescence. In these phosphors, Eu2+ ions play the role activators. Dy3+ ions generate the hole traps that lead to the long persistent phosphorescence and act as the activators in the phosphors simultaneously. The concentration of Dy3+ ions co-doped has a strong influence on the luminescence of phosphor.